Cytotoxicity of Sodium Bicarbonate Solution to Human Gingival Fibroblast Cells - Mahmiyah, Erma; Susatyo, Jojok Heru; Ningsih, Neny Setiawaty (JURNAL INFO KESEHATAN, 2023)
Immunoglobulin A (IgA) is a crucial antibody originating in mucosal lymphoid tissue, actively distributed across the epithelium. It plays a vital role in binding to and neutralizing microbes that threaten organisms through mucosal organs, thereby contributing to mucosal or secretory immunity. This research aims to determine the Cytotoxicity of Sodium Bicarbonate Solution to Human Gingival Fibroblast Cells.  The research method used to investigate the safety and efficacy of various sodium bicarbonate concentrations, we conducted a laboratory experimental study utilizing a post-test-only control group design. Sodium bicarbonate solutions with concentrations of 1%, 2%, 3.5%, 7%, 10%, 15%, and 20% were tested. The results of the study using analysis through ANOVA followed by Tukey HSD revealed that solutions with concentrations of 20%, 15%, and 10% exhibited comparable non-toxicity to fibroblast cells, as they shared the same column. In contrast, concentrations of 7%, 3.5%, 2%, and 1% were found to have toxicity levels that exceeded the IC50 threshold. Further examination using the Tukey HSD test showed that the 2% and 3.5% concentration groups did not show significant differences. In conclusion, the Sodium bicarbonate solutions with concentrations of 7%, 3.5%, 2%, and 1% are not toxic to fibroblast cells and can be used as a basis for further research applications based on sodium bicarbonate materials. It is recommended for future studies to conduct further examinations with different concentrations.